Pattern of Skin Diseases in Al Baha Region of Saudi Arabia: Life Sciences-Health - MD, Azza S. Zahrani; MD, Abdullah M Adnan; MD, Asma G Sadeq; MD, Nesreen Al Umair (International Journal of Life Science and Pharma Research, 2022)
With regard to dermatological diseases, knowledge of the prevalence of diseases would provide the dermatologist with sufficient background information to make an accurate diagnosis.The objective of the study is to determine the prevalence of dermatological diseases in Al-Baha region, and compare this to that reported in other regions of Saudi Arabia. The study included all new cases of skin diseases that were seen at the dermatology outpatient clinic in King Fahad Hospital, Al Baha, from January 1, 2014 to December 31, 2016. Data were collected from the patients’ medical records, and the diagnosis was made by either a dermatology consultant or specialist according to the International Classification of Diseases (ICD-10). A total of 3153 patients were included in this study, and the dermatological diseases were categorized into ten groups. Eczema had the highest prevalence (24.33%), followed by acne (17.36%), viral infections (11.1%), pigmentary disorders (7.04%), papulosquamous diseases (5.7%), fungal infections (5.28%), alopecia and urticaria (equally prevalent, 5.18%), and parasitic infection (1.37%). The remaining 619 patients (19.6%) had a dermatological diagnosis that fell into the ‘miscellaneous’ category. The results of this study were comparable to those of similar studies performed in other regions in Saudi Arabia. Eczema was the most frequent dermatological disease in Al- Baha.